2008
DOI: 10.1139/t07-078
|View full text |Cite
|
Sign up to set email alerts
|

Shear banding and cross-anisotropic behavior observed in laboratory sand tests with stress rotation

Abstract: Shear banding in Santa Monica beach sand deposited by dry pluviation in hollow cylinder specimens is studied in 34 drained torsion shear tests with rotation of principal stress directions. The effect of the specimen height on the soil behavior was investigated by testing specimens with heights of 40 and 25 cm. Each test was conducted with the same, constant inside and outside confining pressure, σr, thus tying the value of b = (σ2– σ3)/(σ1 – σ3) to the inclination, β, of the major principal stress. Shear bands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…Abelev & Lade (2003) and Lade et al (2008) 130 performed different tests on sand with rotation of principal stress axes with regard to the isotropic planes of the material. They concluded that the material strength (peak value) as well as the shear band inclination and pattern may vary with the direction of loading (Fig.…”
Section: Laboratory Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abelev & Lade (2003) and Lade et al (2008) 130 performed different tests on sand with rotation of principal stress axes with regard to the isotropic planes of the material. They concluded that the material strength (peak value) as well as the shear band inclination and pattern may vary with the direction of loading (Fig.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…The influence of cross-anisotropy on the material behaviour and on the shear 20 strain localisation has been investigated by different authors (Abelev & Lade, 2003;Tejchman et al, 2007;Lade et al, 2008). They concluded that the material strength as well as the shear band pattern on small-scale specimens may vary with the direction of loading or with the orientation of the bedding planes.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive phenomenological observations on soil strength and loading path dependence have been made in HCA (Nakata et al 1997;Miura and Toki 1986;Gutierrez et al 1991;Lade et al 2008;Cai et al 2013). Clear evidence of material deformation non-coaxiality, an interesting phenomenon firstly reported by Roscoe (1967) as the non-coincidence of the principal strain rate directions and the principal stress directions has been obtained from HCA testing (e.g.…”
Section: ! Introductionmentioning
confidence: 95%
“…Oda et al 1978;Tatsuoka et al 1990, Alshibli andSture 2000;Wanatowski and Chu 2006), directional shear cells (Phillips and May 1967;Oda and Konishi 1974a, b;Wong and Arthur 1985), true triaxial apparatuses (Arthur and Menzies 1972;Yamada and Ishihara 1979;Ochiai and Lade 1983;Miura and Toki 1984;Abelev and Lade 2004) and hollow cylinder apparatuses (e.g., Symes et al 1988;Miura and Toki 1986;Vaid et al 1990;Gutierrez et al 1991;Nakata et al 1998;Rolo 2003;Lade et al 2008;Cai et al 2013). …”
Section: ! Introductionmentioning
confidence: 99%
“…This may be attributable to different formations of shear band in true triaxial tests and in plane strain tests (Lam and Tatsuoka 1988;Tatsuoka et al 1990). In addition to the fabric anisotropy, the strength of the soil may also be affected by shear band formation, as observed by Lade et al (2008).…”
Section: Toyoura Sandmentioning
confidence: 96%